2017
DOI: 10.1007/s00464-017-5850-0
|View full text |Cite
|
Sign up to set email alerts
|

The trend toward minimally invasive complex abdominal wall reconstruction: is it worth it?

Abstract: Despite an increase in operating room supply costs, transition to performing MIS AWR in cases that were previously done through an open approach decreased LOS and translated into significant overall total cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…8 A recent study demonstrated that minimally invasive AWR had a significantly decreased length of stay compared with open AWR. 9 In addition, robotic retromuscular ventral hernia repair was shown to be associated with decreased length of stay (LOS) compared with open repair 10 and robotic TAR was associated with decreased wound complication rates, morbidity, and LOS compared with open repair. 1012 This report describes the early experience and short-term outcomes of robotic TAR and r-AWR for repair of complex ventral hernias performed by a single surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…8 A recent study demonstrated that minimally invasive AWR had a significantly decreased length of stay compared with open AWR. 9 In addition, robotic retromuscular ventral hernia repair was shown to be associated with decreased length of stay (LOS) compared with open repair 10 and robotic TAR was associated with decreased wound complication rates, morbidity, and LOS compared with open repair. 1012 This report describes the early experience and short-term outcomes of robotic TAR and r-AWR for repair of complex ventral hernias performed by a single surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other literature for abdominal wall reconstruction, overall the number of days was increased in both groups. Other institutions have also noted decreased hospital stay length, although approximately 1–2 days for robotic repairs and up to 5 days for open repairs 2 , 6 , 8 , 10 . At our institution, those receiving open approaches are routinely given an epidural and pump-controlled analgesia (PCA), which may contribute to a longer hospital stay due to pain control weaning parameters and pain management expectations.…”
Section: Discussionmentioning
confidence: 97%
“…Cost analysis would also be a crucial element to investigate in future studies. Belyansky suggested the additional operating time was more than offset by the reduction in hospital days, with overall costs for minimally invasive group being almost half of the open repair 2 . While operating times contribute heavily to costs, whether this outweighs the difference in hospital days could argue for one approach over the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation